Polymorphisms at the 3′ untranslated region of SLC11A1 gene are associated with protection to Brucella infection in goats - Iacoboni, Paola Anabella; Hasenauer, Flavia Carolina; Caffaro, María Eugenia; Gaido, Analia Beatriz; Rossetto, Cristina; Neumann, Roberto Daniel; Salatin, Antonio Omar; Bertoni, Emiliano Agustín; Poli, Mario Andres; Rossetti, Carlos Alberto (Elsevier, 2019)
Goats are susceptible to brucellosis and the detection of Brucella-infected animals is carried out by serological tests. In other ruminant species, polymorphisms in microsatellites (Ms) of 3′ untranslated region (3′UTR) of the solute carrier family 11 member A1 (SLC11A1) gene were associated with resistance to Brucella abortus infection. Goats present two polymorphic Ms at the 3′UTR end of SLC11A1 gene, called regions A and B. Here, we evaluated if polymorphisms in regions A and/or B are associated with Brucella infection in goats. Serum (for the detection of Brucella-specific antibodies) and hair samples (for DNA isolation and structure analysis of the SLC11A1 gene) were randomly collected from 229 adult native goats from the northwest of Argentina. Serological status was evaluated by buffer plate antigen test (BPAT) complemented by the fluorescent polarization assay (FPA), and the genotype of the 3′UTR of the SLC11A1 gene was determined by capillary electrophoresis and confirmed by sequence analysis. Polymorphisms in regions A and B of the 3′UTR SLC11A1 gene were found statistically significant associated with protection to Brucella infection. Specifically, the association study indicates statistical significance of the allele A15 and B7/B7 genotype with absence of Brucella-specific antibodies (p = 0.0003 and 0.0088, respectively). These data open a promising opportunity for limiting goat brucellosis through selective breeding of animals based on genetic markers associated with natural resistance to B. melitensis infection.